2021
DOI: 10.3390/ani11020538
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sedation with Medetomidine and Dexmedetomidine on Doppler Measurements of Ovarian Artery Blood Flow in Bitches

Abstract: The aim was to evaluate if medetomidine and dexmedetomidine affected arterial ovarian blood flow in dogs. The dogs were randomly assigned to two different groups. In Group 1, medetomidine (10 µg/kg) was administered intramuscularly and, in Group 2, dexmedetomidine (5 µg/kg) was used. After a preliminary exam, arterial blood pressure (BP) was measured and a duplex Doppler ultrasonographic examination of both ovarian arteries was performed. Twenty minutes after the administration of medetomidine or dexmedetomidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…maternal heart rates were substantially lower in the sedated conditions compared to the non-seated conditions. In general, alpha 2-adrenoceptor agonists (such as xylazine) cause a peripheral phase of vasoconstriction, hypertension, and reflex bradycardia, followed by a central phase or effect of decreased sympathetic tone, bradycardia (decreased heart rate), and hypertension (Nicolás-Barceló et al 2021 ). A previous investigation on goats found that xylazine sedation significantly reduced heart rate, cardiac output, and Doppler hemodynamic parameters of the pulmonary artery, aortic, and mitral inputs (Mandour et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…maternal heart rates were substantially lower in the sedated conditions compared to the non-seated conditions. In general, alpha 2-adrenoceptor agonists (such as xylazine) cause a peripheral phase of vasoconstriction, hypertension, and reflex bradycardia, followed by a central phase or effect of decreased sympathetic tone, bradycardia (decreased heart rate), and hypertension (Nicolás-Barceló et al 2021 ). A previous investigation on goats found that xylazine sedation significantly reduced heart rate, cardiac output, and Doppler hemodynamic parameters of the pulmonary artery, aortic, and mitral inputs (Mandour et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of xylazine resulted in decreased stress levels (lower cortisol levels) during the laparoscopic embryo transfer and enhanced the pregnancy rate of recipient goats (Aghamiri et al 2022 ). Administration of medetomidine or dexmedetomidine (alpha 2 agonist sedatives like xylazine) in bitches significantly decreased the blood flow to the ovarian arteries and may be a wise alternative to prevent excessive bleeding before the ovariectomy (Nicolás-Barceló et al 2021 ). Sedation of animals may be important, especially during the late gestation stage and handling of dystocia cases, to minimize the anxiety fear, and distress, and to facilitate the successful performance of diagnostic or therapeutic procedures, and during conservative or surgical obstetrical procedures, providing patient comfort and cooperation.…”
Section: Introductionmentioning
confidence: 99%